The results of the toxicologycal assesment of exhausted detergent solutions - Букатенко, Наталья Алексеевна; Васьковец, Людмила Антоновна (Eastern-European Journal of Enterprise Technologies, 2012)
After automobiles wash, exhausted detergent solutions contain suspended substances, petroleum products and synthetic surface-active substances. Petroleum products and synthetic surface-active substances present the largest ecological danger. To purify exhausted detergent solutions it is important to determine their composition, level of contamination and to establish the toxicological assessment. Therefore, to guarantee ecological safety of environment the norms of limit permissible escape of contaminations in the water are established. The experiments on toxicological assessment of exhausted detergent solutions were performed to determine their extent danger. The analyses were carried out according to the biotesting methodology of the crawfish-like (Daphnia). The laboratory crop Daphnia magna Straus was used as the test object. The results of the toxicological assessment indicate that the dilution of exhausted detergent solutions with water cannot guarantee ecological safety. The special technological plan for purification of detergent solutions is necessary.